2017
DOI: 10.1007/s00109-017-1586-5
|View full text |Cite
|
Sign up to set email alerts
|

NEAT1 accelerates the progression of liver fibrosis via regulation of microRNA-122 and Kruppel-like factor 6

Abstract: NEAT1 was significantly increased in CCl-induced mice and activated HSCs. Loss of NEAT1 suppressed liver fibrosis in vivo and in vitro. KLF6 and miR-122 were required for the effects of NEAT1 on HSC activation. NEAT1 contributes to HSC activation via competitively binding miR-122. We disclose a novel NEAT1-miR-122-KLF6 signaling cascade.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
69
0
3

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 80 publications
(77 citation statements)
references
References 44 publications
4
69
0
3
Order By: Relevance
“…NEAT1 showed highly variable expression levels in the SN, which may reflect its reaction to a wide variety of stimuli, including estrogen (25), hepatic fibrosis (59), oxidative stress, and treatment with various therapeutics including simvastatin and fenofibrate (this study)—possibly through the effects of these drugs on the activity of transcription factors of the PPAR family (60, 61), binding sites for which and for their interactor retinoid X receptor-α lie upstream to the NEAT1 transcription start site (47, 62). This offers another mechanism to explain the neuroprotective traits of these drugs (16, 60, 63, 64) and calls for investigating the effects of additional blood-brain barrier–penetrable agents on NEAT1 levels.…”
Section: Discussionmentioning
confidence: 99%
“…NEAT1 showed highly variable expression levels in the SN, which may reflect its reaction to a wide variety of stimuli, including estrogen (25), hepatic fibrosis (59), oxidative stress, and treatment with various therapeutics including simvastatin and fenofibrate (this study)—possibly through the effects of these drugs on the activity of transcription factors of the PPAR family (60, 61), binding sites for which and for their interactor retinoid X receptor-α lie upstream to the NEAT1 transcription start site (47, 62). This offers another mechanism to explain the neuroprotective traits of these drugs (16, 60, 63, 64) and calls for investigating the effects of additional blood-brain barrier–penetrable agents on NEAT1 levels.…”
Section: Discussionmentioning
confidence: 99%
“…Nuclear-enriched abundant transcript 1 (NEAT1) is located in 11q13 [128]. The expression of NEAT1 was found to be increased in primary HSCs derived from CCl4-treated mice compared to control mice [74]. NEAT1 overexpression promoted the activation of HSCs and increased levels of Actα2 and Col1α1, indicating that this lncRNA plays a role in HSC activation [36].…”
Section: Neat1mentioning
confidence: 99%
“…NEAT1 overexpression promoted the activation of HSCs and increased levels of Actα2 and Col1α1, indicating that this lncRNA plays a role in HSC activation [36]. NEAT1 overexpression corresponded with decreased levels of miR-122, which was identified to regulate NEAT1 effects on the activation of HSCs by a mechanism associated with Kruppel-like factor 6 (Klf6) [36,74]. The expression of NEAT1 was up-regulated in HCC, while its knockdown was correlated with decreases not only in HCC cell proliferation, but with also invasion, and migration via regulating heterogeneous nuclear ribonucleoprotein A2 (hnRNP A2) [75].…”
Section: Neat1mentioning
confidence: 99%
“…In addition, NEAT1 also played an important regulatory role in some diseases, such as acute kidney injury [14], neuropathic pain [15] and liver fibrosis [16]. Previous study has shown that NEAT1 was overexpressed in AAA [17]; nevertheless, the function and mechanism of NEAT1 in AAA remain obscure.…”
Section: Introductionmentioning
confidence: 99%